Em nome do Pai: Memórias do projeto em Direitos Humanos “Nome Legal” do Ministério Público da Paraíba (2011 – 2015) - Nascimento, Guilherme Pinto do (2018)
The Permanent Parenting Core “Nome Legal” created by the Public Ministry of Paraiba appeared in 2015 as a way of effectuation and institutionalization of the practices of the same name project, being this one developed as a result of the alarming numbers from the school census of the National Council of Justice in 2011, shows that 5,5 million children did not have their father‟s name on the birth certificate. The study objective is analyze the Permanent Parenting Core, considering the participants memories, connecting with Public Ministry developed actions and the perspective of family and paternity, by a project in human rights. About the methodology, a qualitative research was done using Oral History‟s proceedings, performing half structured interviews. Nevertheless the international rules about children rights protection exist since 1924, Brazil was a lingerer in this aspect, because it only had regulated the child and the juvenil, as a right subject, gifted with full protection, in 1988 with the current Federal Constitution, constituting in the Child and Adolescent Statute in 1990. By the project analysis, is perceived that a “beyond the court” acting of the Public Ministry has a great relevance in the implementation and consolidation of the child and adolescents rights, mostly in the reason by the damage caused by the judicialization. The memory, according to Le Goff (1990), Pollak (1992), Leal (2016) and others, in “association” with the oral history and the present time history, were indispensable devices of research and comprehension in this study, because they contributed to the building of a more complete and equanimous history, without manipulation or oblivion impositions, attributing importance to every event. So, it is able to conclude that the ministerial performance – and the task force set up by the Public Ministry – was directly responsible for improving the family situation in the state of Paraíba, contributing to a paradigm shift related to fatherhood, based (mainly) on the affection, collaborating to the gradual redetermination of the patriarchal family model, although it has solid roots.